Answer:
The solution to the system of equations is x=3 y= 23
Explanation:
solving this system of equation using substitution method
-3x-y=14 ….. equation (1)
-9x =-27 ….. equation (2)
Solving for value of x from equation 2
-9x =-27
so x= -27/-9 = 3
so x = 3
The second equation is solved for x, so we can substitute the expression 3 in for x in the first equation (1)
-3x-y=14
-3 (3) + y =14
-9+y= 14
y=14+9
y=23
The solution to the system of equations is x=3 y= 23
We can check our work by plugging these numbers back into the original equations. Let's try -3x-y=14
-3x-y=14
-3(3) -23= 14
-9+23 = 14
14= 14
Yes, our solution checks out.